Il caso di Jackie the Baboon: Dalla teoria della performance agli Animal Performance Studies - Budriesi, Laura (Mimesis Journal, 2019)
The performance Jackie the Baboon of the British company Brunskill & Grimes tells the true story of the baboon Jackie who was forced to participate in the First World War. The show is part of a project of the University of Surrey, coordinated by Laura Cull, philosopher of the performance, which combines philosophical reflection and performances, related to theory as well as the practice of Animal Performance Studies. This research path takes place in a field of studies not much frequented in Italy, that of Animal Performance Studies. In this context, performance is understood as a method of research aimed at finding answers to the animal question, through the same performance practice and to explore new relational modalities among different species. This field of research had already been opened by Richard Schechner who in the theory of performance included the activities of the primates in the broad spectrum of performing activities.